Cross-Section Production Functions and the Elasticity of Substitution in American Manufacturing Industry - Ferguson, C. E. (The Review of Economics and Statistics, 1963)
C. E. Ferguson, Cross-Section Production Functions and the Elasticity of Substitution in American Manufacturing Industry, The Review of Economics and Statistics, Vol. 45, No. 3 (Aug., 1963), pp. 305-313